Range Extension of Borehole Strainmeters Using MOSFET-Based Multi-Switch Automatic Zero Setting - Chen Yang; Zheng Chen; Hong Li; Wenbo Wang; Weiwei Zhan; Liheng Wu; Yunkai Dong; Jiaxin Chen (Sensors)
Borehole strainmeters are essential tools for observing crustal deformation. In long-term observational applications, the dynamic changes in crustal deformation over multi-year scales often exceed the single measurement range of borehole strainmeters. Expanding the measurement range while maintaining high precision is a critical technical challenge. To address this, a full-range measurement system was developed using a bidirectional analog multi-switch based on MOS transistors and automatic feedback control. This system automatically adjusts the zero point of the measurement bridge, maintaining the bridge output at a near-balanced state. The quantifiable zero-setting actions are dynamically converted into equivalent voltage, enabling automatic full-range measurements while fully utilizing the effective linear range of the differential capacitive sensors. A laboratory performance tests demonstrated that an RZB borehole strainmeter equipped with this automatic zero-setting range extension system successfully covers the differential capacitive sensor’s effective linear range of approximately 100 μm.